Depois da Graduação: Inserção Profissional de Egressos do Curso de Música – Licenciatura da UNIPAMPA - Henrique, Andreivis Rufino (2022)
Inspired by Solange Maranho Gomes’ work, this research aims to understand the professional integration of professional who had their degree on Music education from Federal University of Pampa (also known as Unipampa) located in the city of Bagé (very south of Brazil). The research has a quantitative approach, is based in a questionnaire constituted of 78 questions inspired by the work of Gomes (2016) and distributed by Goggle Forms platform. Out of 32 former students (who had their degree until 2019) we obtained 20 answers (62,5%). Through the acquired data we could see a concentration in professional integration as instrumentalist, arranger and composer. We have also identified the integration as a teacher by 8 out of 20 respondents (40%) which demonstrates a need for professionals in this field. The Bagé region is shown to be a place in need of professionals in this field, since the egressed students who were not originally from the city continued to reside there after the completion of the course. Another factor that contributes to this finding is the majority of the egressed students claims they feel professionally recognized. The results from the research represents a potential for use in the institutional evaluation practices in the course and contribute to the field of research on the professional insertion of professionals with higher education in Music in Brazil.